ChemInform Abstract: Asymmetric Synthesis of Tetrahydropyridines via a Broensted Acid Catalyzed Aza‐Diels—Alder Reaction. Issue 16 (March 2016) - Beceno, Christian; Krappitz, Tim; Raabe, Gerhard; Enders, Dieter
Abstract: Protected glyoxylate imine reacts with various aryl substituted 2‐silyloxy‐1, 3‐butadienes, and depending on the functionalization of the aryl ring tetrahydropyridines are obtained.